Assessing Work Environment, Organizational Culture, and Job Satisfaction of Hotel Employees - Iwan Boediherwanto; Boge Triatmanto; Bambang Supriadi (Trescode Green Organization, 2024)
This research aims to describe the variables of work environment, organizational culture, job satisfaction of hotel employees in Yogyakarta. This explanatory research emphasizes explaining the relationship between work environment variables, organizational culture, and job satisfaction for hotel employees. Location This research was conducted on hotel employees in Yogyakarta because hotel employees in Yogyakarta remember that the number of hotel employees experienced a decline in 2019 and 2022 due to the impact of the pandemic and Yogyakarta has a high workload because it is one of the main tourist destination cities on the island of Java. The population of this study were all hotel employees in Yogyakarta, totaling 4,524 employees, who had a minimum work period of 5 years with a sample size of 150 people. The research results show that infrastructure facilities, harmonious working relationships with superiors, health facilities, and security protection shape the hotel work environment in Yogyakarta. Organizational culture is formed by the freedom to innovate, completing work with a team, working based on guidelines, and a shared understanding of work. Job satisfaction at hotels in Yogyakarta is formed by expectations, enjoying work, work achievements, promotional opportunities, job appreciation, and support from colleagues. This research is expected to positively contribute to discussing the work environment, applying organizational cultural values, and job satisfaction, especially in hotel services companies.